Measuring the Effects of Monetary Policy in the Euro Area: The Role of Anticipated Policy - Jan Gottschalk; Florian Höppner (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
This paper investigates within a SVAR framework the effects of anticipated monetary policy in the euro area. Building on a procedure recently proposed by Cochrane yielding the response of output to an anticipated monetary policy impulse, we show that in the past twenty years anticipated monetary policy had a considerable influence on output. Moreover, we compute the output effects of the systematic monetary policy response to aggregate demand and supply shocks. We find that monetary policy pursues a counter-cyclical policy in response to demand shocks and is pro-cyclical with regard to supply shocks, even though there are considerable lags.
Keywords: E52; C32; C52; 330; Vector Autoregression; Systematic Monetary Policy; Historical Decomposition